"Extroverted Cuff", a novel modification of the elephant trunk technique for distal anastomosis of ragged descending aorta. Issue 1 (December 2016) - Prifti, Edvin; Veshti, Altin; Ademaj, Fadil; Baboci, Arben
Abstract Background The elephant trunk technique has been applied in various situations including distal aortic dissection, entire aortic replacement, proximal aortic aneurysm, proximal aortic dissection, and Marfan's syndrome. The elephant trunk technique remains a challenge in cardiac surgery. Here we report a modification of this surgical approach. Case presentation The "extroverted cuff" technique that we propose is a novel modification of the flanged technique for the elephant trunk construction. The technique consists in the graft extroversion which is than located inside the descending aorta. Then the distal anastomosis is constructed between the descending aorta and the circular free edge the external layer of the graft. Such a technique was successfully applied in a patient with type A aortic dissection undergoing modified elephant trunk technique, aortic arch replacement and Bentall operation. Conclusion Such a modification seems suitable for aortic arch aneurysm with ragged descending thoracic aorta that minimizes bleeding from the distal anastomosis and potentially prevents distal embolization of atheromatous plaque.